2022
DOI: 10.1103/physrevb.105.064429
|View full text |Cite
|
Sign up to set email alerts
|

Local control of magnetic interface effects in chiral Ir|Co|Pt multilayers using Ga+ ion irradiation

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
4
10
0
Order By: Relevance
“…As ID N increased, the D value decreased from 0.49 to 0.22 mJ·m –2 . This decreasing trend is similar to that observed in other ion-implanted multilayer systems. ,, The DMI diminution may originate from the atomic interdiffusion at the Pt/Co interface during the implantation of N ions …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As ID N increased, the D value decreased from 0.49 to 0.22 mJ·m –2 . This decreasing trend is similar to that observed in other ion-implanted multilayer systems. ,, The DMI diminution may originate from the atomic interdiffusion at the Pt/Co interface during the implantation of N ions …”
Section: Resultssupporting
confidence: 87%
“…In previous studies, strain was the conventional scheme to tune the lattice attribute, and it could induce obvious modifications on both the DMI and magnetic anisotropy of skyrmion-hosting films based on the magnetoelastic effect. However, the application of strain on the films required a stretchable substrate (e.g., ferroelectrics, shape memory alloy, and flexible polymer), posing a great challenge concerning compatibility with modern large-scale integrated circuit technology (LSICT). An alternative strategy for lattice modification is to introduce lattice defects (e.g., vacancies and interstitials), which have been demonstrated to be able to significantly affect the Heisenberg exchange interaction, magnetic anisotropy, and DMI. Thus, the skyrmion nucleation is expected to be controllably manipulated through appropriate defect engineering. More importantly, this strategy does not rely on any special substrate, showing better compatibility with modern integrated circuit technology.…”
Section: Introductionmentioning
confidence: 99%
“…1e. We found that the PMA decreases monotonically with irradiation fluence, which is consistent with earlier studies 24,35 . Here, we specifically note that PMA persists up to a very large degree of intermixing (irradiation fluence), which is much higher than previous studies on ferromagnets 24,28,36 .…”
supporting
confidence: 93%
“…It is well known that ion irradiation is an excellent tool to tune locally the magnetic and structural properties of thin films through ordering [13][14][15][16] and interface intermixing [17][18][19][20] . In Permalloy films, ion irradiation has been shown to change the magnetic anisotropy [21][22][23] and the magneto-resistive response in the presence of exchange bias 4,24 .…”
Section: Introductionmentioning
confidence: 99%